Motivasi Internal dan Eksternal Siswa Sekolah Dasar pada Pembelajaran Matematika - Ni Luh Sakinah Nuraini; Wisnu Cahyo Laksono (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2019)
One of the factor that plays an important role in learning mathematics is motivation to learn. The purpose of this study was to determine learning motivation both internal and external motivation that play a role in student learning in the content of mathematics in SDN 1 Gawang and SDN 2 Gawang, Kebonagung District, Pacitan Regency. The results showed that the internal motivation and external motivation of students of SDN 1 Gawang and SDN 2 Gawang in learning mathematics were in the good category, based on the average scores obtained. Viewed from the supporting indicators, it is necessary to increase internal motivation related to expectations while learning and external motivation related to an adequate learning environment in mathematics learning. In addition, specifically at SDN 2 Gawang, the provision of external motivation still needs to be improved in order to optimize learning of mathematics, especially in fourth grade students. Salah satu faktor yang memegang peranan penting dalam pembelajaran matematika adalah motivasi belajar. Tujuan penelitian ini adalah untuk mengetahui motivasi belajar baik motivasi internal maupun eksternal yang berperan dalam pembelajaran siswa pada muatan matematika di SDN 1 Gawang dan SDN 2 Gawang, Kecamatan Kebonagung, Kabupaten Pacitan. Hasil penelitian menunjukkan bahwa motivasi internal dan motivasi eksternal siswa SDN 1 Gawang dan SDN 2 Gawang dalam pembelajaran matematika berada pada kategori baik, berdasarkan rata-rata skor yang diperoleh. Dilihat pada indikator pendukungnya, maka perlu ada peningkatan motivasi internal terkait harapan saat belajar dan motivasi eksternal terkait lingkungan belajar yang memadai pada pembelajaran matematika. Selain itu, khusus di SDN 2 Gawang, pemberian motivasi eksternal masih perlu ditingkatkan agar dapat mengoptimalkan pembelajaran matematika, khususnya pada siswa kelas IV.